Introducing the context: local and international trends at the Dictionary of Danish Insular Dialects in the 1920s and 1930s - Hovmark, H (2010)
The Dictionary of Danish Insular Dialects (DID; in Danish: Ømålsordbogen) describes Danish dialects on Zealand, Funen and surrounding islands. It covers the period from 1750 to 1945, the core period being 1850 to 1920. Publishing began in 1992. Since then, a volume has appeared biannually. The plans for and work with DID gathered speed in the 1920'ies and 1930'ies, and a range of new methods and tools were elaborated and brought to use. These tools were inspired by the German so-called Wörter und Sachen-tradition that stressed the importance of ethnological or encyclopaedic aspects in lexicographical descriptions. And, indeed, special ethnological descriptions are to be found in DID (cf. for instance entries like bage 'bake' and høst 'harvest'). These descriptions are rather unique since they on the one hand appear like encyclopaedic articles, but at the same time are making constant reference to the dialectal vocabulary. In this presentation, however, I shall show that other scientific trends also made an important imprint on the new tools and the final planning of the dictionary. For instance, the keen interest in material culture and terminology had strong paralles within ethnology (for instance at the National Museum of Denmakr); and new trends within dialectology had ever since the early 1920'ies stressed the importance of taking into account the communicative and cultural context in the description of the dialects. Special attention will be given to the practical and theoretical considerations behind the so-called big questionnaire, introduced in 1926. Examples of the work with and results of the collection of data using the big questionnaire will be given.